Molecular characterization of ligand selectivity of the sex peptide receptors of Drosophila melanogaster and Aedes aegypti. (December 2020) - Lee, Jae-Hyuk; Lee, Na-Rae; Kim, Do-Hyoung; Kim, Young-Joon
Abstract: Drosophila melanogaster sex peptide receptor ( Drm SPR) is a G protein-coupled receptor (GPCR) with 'dual ligand selectivity' towards sex peptide (SP) and myoinhibitory peptides (MIPs), which are only remotely related to one another. SPR is conserved in almost all the sequenced lophotrochozoan and ecdysozoan genomes. SPRs from non-drosophilid taxa, such as those from the mosquitoes Aedes aegypti ( Aea SPR), Anopheles gambiae ( Ang SPR), and the sea slug Aplysia californica ( Apc SPR), are highly sensitive to MIP, but not to SP. To understand how Drosophila SPRs evolved their SP sensitivity while maintaining MIP sensitivity, we examined ligand selectivity in a series of chimeric GPCRs that combine domains from the SP-sensitive Drm SPR and the SP-insensitive Aea SPR. We found replacement of Pro 238 (P238) in Drm SPR with the corresponding residue from Aea SPR (L310) reduced its SP sensitivity 2.7 fold without altering its MIP sensitivity. The P238 residue located in the third extracellular loop (ECL3) is conserved in Drosophila SPRs and in SPR from the moth Bombyx mori ( Bom SPR), which is considerably more sensitive to SP than Aea SPR, Ang SPR, or Apc SPR. We found, however, that rather than improving Aea SPR's sensitivity to SP, replacement of L310 in Aea SPR with Pro significantly reduces its MIP sensitivity. Thus, our identification of a single amino acid residue critical for SP sensitivity, but not for MIP sensitivity is an important step in clarifying how Drm SPR evolved the ability to detect SP. Graphical abstract: Image 1 Highlights: The Pro 238 (P238) residue in Drosophila melanogaster sex peptide receptor ( Drm SPR) is important for SP sensitivity. The Phe 224 (F224) and Pro 229 (P229) residues in Drm SPR are important for MIP sensitivity. The Leu 296 (L296), Thr 301 (T301), and Leu 310 (L310) residues in Aedes aegypti SPR ( Aea SPR) are important for MIP sensitivity.